Pharmacologic Management of Nonvariceal Upper Gastrointestinal Bleeding - Jeong Hwan Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Acute non-variceal upper gastrointestinal bleeding, the most common etiology of which is peptic ulcer disease, remains a persistent challenge despite a reduction in both its incidence and mortality. Both pharmacologic and endoscopic techniques have been developed to achieve hemostasis, with varying degrees of success. Among the pharmacologic therapies, proton pump inhibitor (PPI) remains the mainstay of treatment with potent acid suppression. Maintenance of the intragastric pH level above 6 by the administration of PPI prevents hemolysis caused by acid or pepsin and thereby promotes aggregation of platelets. Intragastric acid suppression can be achieved more effectively with continuous intravenous infusion of PPI after intravenous bolus injection. A high dose intravenous PPI is effective in reducing the risk of rebleeding, the need for surgery and repeated endoscopy. However, data regarding non-high dose intravenous PPIs are limited. In the future, novel PPIs and potassium-competitove acid blocker are in the area of interest. Combination therapy with the use of endoscopic hemostatic treatment and intravenous PPI administration is known to result in the best outcome for non-variceal upper gastrointestinal bleeding.